2013
DOI: 10.1016/j.yjmcc.2013.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Volume overload induces differential spatiotemporal regulation of myocardial soluble guanylyl cyclase in eccentric hypertrophy and heart failure

Abstract: Nitric oxide activation of soluble guanylyl cyclase (sGC) blunts the cardiac stress response, including cardiomyocyte hypertrophy. In the concentric hypertrophied heart, oxidation and re-localization of myocardial sGC diminish cyclase activity, thus aggravating depressed nitric oxide–cyclic guanosine monophosphate (NO–cGMP) signaling in the pressure-overloaded failing heart. Here, we hypothesized that volume-overload differentially disrupts myocardial sGC activity during early compensated and late decompensate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…Similar to other MAPKs, in vivo and in vitro studies demonstrated that various hypertrophic stimuli and growth factors rapidly and transiently enhanced ERK5 activity in cultured cardiomyocytes (Ikeda et al, 2005, Nicol et al, 2001) and intact hearts (Takeishi et al, 2001, Kacimi and Gerdes, 2003). Recent studies in dogs demonstrated that volume overload-induced eccentric hypertrophy increased the localization of p-ERK5 in caveolae and selectively activated ERK5 signaling (Liu et al, 2013). However, the progression of hypertrophy to HF reduced ERK5 activity to normal levels (Kacimi and Gerdes, 2003), or even lower levels (Takeishi et al, 2002).…”
Section: Mapks In Chronic Cardiac Stress (Hypertrophy and Heart Famentioning
confidence: 99%
“…Similar to other MAPKs, in vivo and in vitro studies demonstrated that various hypertrophic stimuli and growth factors rapidly and transiently enhanced ERK5 activity in cultured cardiomyocytes (Ikeda et al, 2005, Nicol et al, 2001) and intact hearts (Takeishi et al, 2001, Kacimi and Gerdes, 2003). Recent studies in dogs demonstrated that volume overload-induced eccentric hypertrophy increased the localization of p-ERK5 in caveolae and selectively activated ERK5 signaling (Liu et al, 2013). However, the progression of hypertrophy to HF reduced ERK5 activity to normal levels (Kacimi and Gerdes, 2003), or even lower levels (Takeishi et al, 2002).…”
Section: Mapks In Chronic Cardiac Stress (Hypertrophy and Heart Famentioning
confidence: 99%
“…Mitral regurgitation (MR) was induced in conditioned mongrel dogs (19–26 kg) by rupturing a papillary chord under fluoroscopy, as previously described [25, 29, 46]. Sixteen dogs underwent chordal rupture and ten unoperated dogs served as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Caveolae-enriched lipid raft fractions (Cav3 + LR) were prepared from snap-frozen LV tissue, using a discontinuous 35–5 % sucrose density gradient ultracentrifugation method as previously described [29, 57]. LV tissue homogenization was carried out on ice, in detergent-free buffer (50 mmol/L Tris–HCl, pH 7.6, 1 mmol/L EDTA, 1 mmol/L DTT, 2 mmol/L PMSF, 50 mmol/L NaF, 1 mmol/L Na Vanadate) with protease inhibitors (Mammalian Cocktail, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheep, pigs, and dogs all have been used for modeling HF [17]. In these models, HF can be induced by tachycardia (i.e., pacing) [33,34], ischemia provoked by either coronary artery occlusion [35,36] or microembolization [37], or volume overload [38,39]. They differ in their pathological characteristics and offer distinct advantages and disadvantages for testing therapies.…”
Section: Large Animal Modelsmentioning
confidence: 99%